TRANSFORMATIONAL RESEARCH OF THE FRAUD TRIANGLE - Mackevičius, Jonas; Giriūnas, Lukas (Ekonomika, 2013)
Abstract. Fraud is one of the most negative factors of society. Because of frauds, some companies experience many financial and even business continuity problems. The article analyses the theory of the fraud triangle and its transformation into a square. Their various elements – motives, possibilities, pressure, rationalisation, incentive and others – suggested by different authors are presented. The article provides a theoretical analysis of fraud scales and their elements: motives, conditions, possibilities, and performance.Key words: fraud triangle, motives for fraud, fraud scales